Site-selective C—H functionalization of pyridines via activated pyridinium intermediates - Hart, Marie A., author; McNally, Andrew, advisor; Bandar, Jeff, committee member; Szamel, Grzegorz, committee member; Hansen, Jeffrey, committee member (Colorado State University. Libraries, 2025)
Pyridines and related azines are ubiquitous in pharmaceuticals and agrochemicals development. Chemists rely on the development of new synthetic methods to modify these heterocycles. Described herein are the development of methods to functionalize azines and convert pyridines and diazines into new heterocycles. Chapter one introduces the importance of pyridines and related heterocycles in pharmaceuticals as well as methods to access and functionalize these molecules. Both classical and contemporary methods for the functionalization of pyridines are discussed to provide context for this work. Chapter two describes methods for regioselective functionalization of pyridines via Zincke imine intermediates. Electrophilic fluorination, aminomethylation, and amination products are accessed through this platform. Chapter three highlights the Zincke imine platform for the formation of 15N pyridine isotopologues. When combined with deuteration methods, [M+2] and [M+3] pyridines are synthesized with high isotope incorporation. Finally, chapter four presents a method for direct, regioselective C4-pyridine amination through N-Tf pyridinium salts. Nucleophilic addition of amines followed by rearomatization of the dihydropyridine intermediate allows for the synthesis of 4-aminopyridines.
Keywords: aminomethylation; isotope exchange; amination; pyridine; fluorination